ANALISIS POTENSI BERWIRAUSAHA PADA KELOMPOK PEREMPUAN DI DESA KENDRAN, SINGARAJA, BALI - Tunjungsari, Hetty Karunia; Victoria Valentina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
This community service activity aims to increase the awareness and understanding of West Jakarta Methodist High School students about risks in entrepreneurship. The background of this activity is based on the importance of equipping students with relevant knowledge and skills to face the challenges of the business world, as well as students' lack of understanding of the risks associated with entrepreneurial activities. The method used is interactive socialization involving lectures, presentations, discussions, and case studies. The participants of the activity were Methodist High School students, with a focus on students in grades X and XII. The results of the activity showed a significant increase in students' knowledge about entrepreneurial risks, as evidenced by the enthusiasm of the participants in participating in the activity and the ability of students to do the assignments in the Worksheet. The evaluation questionnaire showed that most students rated the material useful, the delivery of the material was easy to understand, and the activities increased their interest in entrepreneurship. Participant observations also showed a high level of student involvement during activities. The conclusion of this activity is that socialization about entrepreneurial risks is effective in increasing students' knowledge and interests. The practical implication is that this activity can be a model for the development of entrepreneurship education programs in other schools. Suggestions for further development include larger-scale research, long-term evaluations, and improvements to materials and delivery methods. Thus, this activity makes a real contribution in preparing students to face challenges in the world of entrepreneurship and encouraging the spirit of entrepreneurship among the younger generation. Kegiatan ini bertujuan untuk menganalisis potensi berwirausaha pada kelompok perempuan di Desa Kendran, Bali. Pengumpulan data dan analisis dilakukan dengan menggunakan pendekatan kualitatif yaitu metode studi kasus. Data dikumpulkan melalui wawancara mendalam dengan informan kunci, observasi partisipan, dan studi dokumen. Hasil kegiatan abdimas menunjukkan bahwa perempuan di Desa Kendran memiliki potensi berwirausaha yang signifikan, didukung oleh beberapa faktor. Pertama, adanya keterampilan tradisional yang relevan dengan kebutuhan pasar, seperti keterampilan membuat kerajinan tangan dan mengolah makanan lokal. Kedua, adanya modal sosial yang kuat dalam bentuk jaringan kekerabatan dan komunitas yang mendukung kegiatan wirausaha. Ketiga, meningkatnya kesadaran akan pentingnya kemandirian ekonomi dan kontribusi terhadap keluarga. Keempat, dukungan dari pemerintah daerah dan organisasi masyarakat dalam bentuk pelatihan, pendampingan, dan akses terhadap modal. Namun, terdapat pula tantangan, seperti keterbatasan akses terhadap informasi pasar, modal usaha, dan teknologi. Kegiatan ini merekomendasikan pentingnya peningkatan kapasitas melalui pelatihan yang berkelanjutan, pengembangan jejaring pemasaran, dan fasilitasi akses terhadap sumber daya finansial untuk mengoptimalkan potensi wirausaha perempuan di Desa Kendran. Implikasi dari kegiatan ini adalah kontribusi terhadap peningkatan kesejahteraan keluarga dan pemberdayaan perempuan secara berkelanjutan.